The development of cost estimation model for Indonesian state building: The case of West Sumatera province / Dwi Fitra Yenti Jumas - Dwi Fitra Yenti, Jumas (2019)
This research is concerned especially on cost factors affecting the accuracy of building construction cost. The aim of the research is to develop the cost estimation model (CEM) for the Indonesian state buildings in order to avoid a large difference between the conceptual cost estimation and the real cost of project which is supposed to be economical and useful for a state building in West Sumatera province. The research has four objectives which include identifying the characteristic of factors affecting the cost of building project, determining the relative importance of the main cost factors or parameters for the incorporation of a CEM in the early stage of the project development, developing a CEM by determining the input each main cost factor or parameter in the model, and establishing the conceptual cost estimation (CCE) model for building project development that can improve the accuracy of cost estimation for building project. The research used the historical project data of 81 new building construction projects in West Sumatera, built from 2005 to 2015. The analysis was able to show the relationship among the fourteen cost factors that indicated three cost factors which had a significant impact for CEM. Therefore, the three cost factors were used in the model development. Two models, the MRA and the integration of MRA and ANFIS (MRANFIS) were applied to predict a more accurate of building cost per gross floor area (GFA). For the optimum model, MRA used fewer variables than ANFIS which were the GFA and the type of roof. On contrary, ANFIS used three variables which were the GFA, the number of stories and the type of roof. Moreover, the MRANFIS model showed a better accuracy in the cost estimation compared to the MRA model with the improvement of 2.9%. The contribution of the research is the development of a reasonably accurate and practical method of systematized CEM that can be used by organizations involved in the planning and execution of building construction projects, especially in the Public Work Department in West Sumatra, Indonesia. It may advise whether the essential budget limit for the proposed project is overestimated and may lead the extra fund to be allocated for other projects. The concepts and methodologies presented in the study can also be readily applied to other similar organizations.